Association of Parents’ Educational Factor with Low Birth Weight of Children in Bangladesh: Analysis from A Nationwide Cross-Sectional Data - Kabir, Md Ahsanul; Tania, Motahara Islam; Hossain, Zenat Zebin (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Low birth weight (LBW) is a leading public health problem especially in a developing country like Bangladesh. Objective: To identify the extend of low birth weight and its associated factors among Bangladeshi children with a countrywide data. Methods: Data were used from Bangladesh demographic and health survey (BDHS) 2017. A total of 2204 child data has been observed and descriptive analyses were performed to determine various social and demographic characteristics. Logistic regression model was used to present Parents’ Education associated with low birth weight and results were described in terms of odds ratio (OR) with 95% CI for both adjusted (aOR) and unadjusted (uOR) models. Results: Prevalence of low birthweight is 21.26% vs 14.11% among the unwanted and wanted children in the rural area and this difference is statistically significant. uOR and aOR of having low birthweight is lower among the children from higher educated mother (aOR=0.48, 95% CI= 0.24, 0.98) and children from richest economic group (aOR=0.52, 95% CI= 0.31, 0.89). This odd is significant in 95% CI (p-value= <0.05) for both adjusted and unadjusted model. Odds of having low birthweight in child is 37% higher (aOR=1.37, 95% CI= 0.75, 2.46) among the unplanned children. This association is statistically significant for both unadjusted and adjusted model (p-value= <0.05). Conclusion: To summarize, the prevalence of low birthweight among children is high in the rural areas in comparison to urban areas in Bangladesh. Children of uneducated and low educated parents are at risk of having low birth weight. Special antenatal care should be given to the mothers who have less educational qualifications. International Journal of Human and Health Sciences Vol. 07 No. 03 Jul’23 Page: 233-238